Radical Subject Acceleration for Gifted Students: One School's Response - Chalwell, Kaye; Cumming, Therese M (Australasian journal of gifted education, 2019)
Radical subject acceleration, or moving students through a subject area faster than is typical, including skipping grades, is a widely accepted approach to support students who are gifted and talented. This is done in order to match the student's cognitive level and learning needs. This case study explored radical subject acceleration for gifted students by focusing on one school's response to the learning needs of a ten year old mathematically gifted student. It provides insight into the challenges, accommodations and approach to radical subject acceleration in an Australian school. It explored the processes and decisions made to ensure that a gifted student's learning needs were met and identified salient issues for radical subject acceleration. Lessons learned from this case study may be helpful for schools considering radical acceleration.